INVESTMENT ATTRACTION OF PROJECTS RELATED TO THE IMPLEMENTATION OF INFORMATION TECHNOLOGIES THE MANAGEMENT OF OIL AND GAS COMPANIES - Фадеева, Ирина (SWorldJournal, 2020)
The general tendencies of scientific and technical development of oil and gas companies are considered in accordance with the strategy of world development of Industry-4.2. The direct and indirect benefits of investing in IT related projects for managing